Urbanization and Regional Imbalances in Indonesia - Saratri Wilonoyudho; R. Rijanta; Yeremias T. Keban; Bakti Setiawan (Indonesian Journal of Geography, 2017)
The level of urbanization that occurred in Indonesia at this time is remarkable that causes the growth of cities very rapidly. The growth of cities is mainly due to various reasons such as the capitalization process, regional enlargement/reclassification, as well as migration from rural to urban. The growth of cities leads a lot of problems like environmental degradation, traffic congestion, poverty, crime and other social conflicts. Such a rapid rate of urbanization is a reflection of the inequity between rural and urban development. Lack of employment opportunities in the village causes the population to go into town to find work. The imbalance of development that occurs is a result of implementing a liberal economic system that only emphasizes growth, while on the other side of the agricultural sector is not paid any appropriate attention. The farmers are at a very weak and do not have a good bargaining position, with the exchange rate is very lame. Even regarding with the foodstuffs such as rice, wheat, sugar, salt, etc., Indonesia has to import from abroad. The imbalances of development do not only occur between rural and urban, but also between Java and the outside of Java, and between western and eastern Indonesia regions. This imbalance should be found a solution, with good management and equitable development, including the political will to reform the economic system in favor of the Indonesian people.